Avaliação química e antioxidante da farinha de yacon (Smallanthus sonchifolius) e sua aplicação na elaboração de hambúrguer - Silva, Camila Giacomelli da (2016)
Considering the demand for fast and easy food preparation, industrial/scientific communities are advancing the development of new products, as well as meet this demand, can offer advantages to consumer health. Thus, this study aimed to characterize the chemical composition, quantify the phenolic and flavonoid, evaluate the antioxidant and antimicrobial potential of yacon flour (Smallanthus sonchifolius) and develop burgers with fat reduction and addition of dietary fiber. Analyses were performed in flour yacon of its chemical composition, antioxidant potential (methods for phenolic compounds, flavonoids, ABTS* + Radical, DPPH and FRAP) and antimicrobial. For the burgers was made a 23 factorial design, with variations fat swine (10, 15 and 20%), flour of yacon (0, 4.5 and 9%) and sodium erythorbate (0, 0.1 and 0.2%), thus presenting 9 formulations and repetitions on the PC (HY9, HY10 and HY11). The analyzes were performed for 120 days (0, 30, 60, 90 and 120), assessing lipid oxidation (TBARS), pH, water activity and color. Still, it was examined technological and sensory parameters. The results showed that the flour yacon has 3.2% moisture, 3.17% ash, 1.04% protein, 0.98% ether extract, 74.25% total dietary fiber (15.00 % insoluble fiber, soluble fiber of 1.64%, 45.45% and 11.96% FOS and inulin), 1.84% starch, 6.35% fructose, 4.4% glucose and 6.07% sucrose. Total phenolics found in the aqueous extract was 39.21 mg GAE/g and hydroethanol extract was 77.24 mg GAE/g. As for total flavonoid, the aqueous extract showed 2.66 mg EQ/g and hydroethanol treatment showed 15.11 mg EQ/g. In relation to the antioxidant potential IC50 values found by DPPH method were 20.32 mg/g and 2.42 mg/g, respectively for aqueous and hydroethanolic. The results of FRAP to aqueous o extract was 0.99 μmol/TEAC.g-1 and hydroethanolic was 7.33 μmol/TEAC.g-1. The ABTS* + radical in the aqueous extract was 1.12 μmol/TEAC.g-1 and hydroethanol was 4.11 μmol/TEAC.g-1. The hydroethanol extract showed the best results for bioactive compounds analyzed, and best antioxidant potential measured by different techniques. The extracts showed no antimicrobial activity. It was found in flour yacon presence of non digestible carbohydrates (74.25%), mainly in the form of FOS and inulin, and also antioxidant capacity, which would bring nutritional and physiological benefits when ingested regularly. The chemical analysis of the burgers have shown that treatments with higher concentrations of the yacon flour and fat had lower moisture (41.95 and 42.91%) to ashes met values from 4.09 to 4.91%, protein 19.30 to 22.20%, and it was possible to prepare formulations with reduced fat without presents discontent by the panel of sensory analysis and burgers adding more flour yacon (9%) may be classified as sources in fiber 100 g of product. On the shelf life of the results of TBARS showed that the meal did not contribute to the oxidation but did not act as an antioxidant. The pH was increased in all treatment and showed a decrease water activity when added to flour yacon. Microbiological results are within the required by brasilian law. The sensorial analysis showed the burgers note 5, score "liked" on structured 7-point scale in all attributes evaluated and tested two days (10 and 90 days). Moreover, the flour yacon contributed yield and lower shrinkage of burgers.